Dysregulated bile acid metabolism drives lipid peroxidation and ferroptosis in NAFLD: therapeutic potential for traditional Chinese medicine - Liu, Jing; Li, Fuxing; Zeng, Qianru; Hu, Wenxiao; Yang, Le; Luo, Shengping; Li, Dingxiang; Deng, Yihui (Frontiers in Pharmacology, 2025)
Non-alcoholic fatty liver disease (NAFLD), characterized by abnormal lipid accumulation in hepatocytes, is prevalent in conditions such as type 2 diabetes mellitus and obesity, which are associated with dysregulated glucose and lipid metabolism. Bile acids (BAs) are critical regulators of lipid and glucose homeostasis. Emerging research suggests that disturbances in BA metabolism not only exacerbate metabolic imbalance but also promote ferroptosis via lipid peroxidation. This review differs by systematically linking BA regulation, ferroptosis, and TCM, highlighting the multi-component and multi-target advantages of TCM in preventing and treating NAFLD. We summarize the mechanisms by which BAs regulate hepatic lipid synthesis and oxidation, and how lipid peroxidation connects to ferroptosis through glutathione/glutathione disulfide (GSH/GSSG) and reactive oxygen species (ROS). Finally, we review studies on TCM modulation of BA metabolism and ferroptosis to improve lipid peroxidation and metabolic disorders, providing timely insights into innovative therapeutic strategies for NAFLD.